Calprotectin in patients with chronic rheumatoid arthritis correlates with disease activity and responsiveness to methotrexate. (17th February 2018) - Nielsen, Ulla Bregendahl; Bruhn, Laerke Valsøe; Ellingsen, Torkell; Stengaard-Pedersen, Kristian; Hornung, Nete
Abstract: Objective: Calprotectin (myeloid-related protein 8/14) is elevated in inflammatory diseases and a correlation of serum calprotectin and disease activity in rheumatoid arthritis (RA) has been shown. In this study, we investigated plasma calprotectin as a disease marker in patients with chronic RA treated with methotrexate (MTX) monotherapy and compared plasma calprotectin with C-reactive protein (CRP) in this matter. Methods: Seventy-six patients with chronic RA were included in this open prospective study and of these 40 were included prior to initiation of MTX therapy. The patients were followed with laboratory and clinical parameters for 52–56 weeks. Plasma calprotectin was analyzed at the start of study and at various intervals. Radiographic evaluation was performed at baseline and after 17.2 months and progression in joint destruction was measured with Larsen score. The response to MTX was evaluated according to the American College of Rheumatology criteria. Results: Patients starting MTX treatment had significantly higher levels of plasma calprotectin compared to patients well established on MTX therapy ( p = .008). Among the 40 patients naive to MTX, 25 responded to MTX therapy and serum calprotectin decreased significantly in these patients ( p = .0007). The radiographic damage showed no relation to calprotectin. Conclusions: Plasma calprotectin is associated with disease activity in patients with chronic RA and is more strongly correlated to MTX response compared to CRP. The role of calprotectin as a disease marker is promising and the advantages compared to CRP needs to be further investigated.